An updated review on microspheres: a suitable drug carrier in sustained release drug delivery - Srivastav, Sachin; Kumar, Kapil; Joshi, Aparna; Teotia, Deepak; Ikram, Ikram (International Journal of Indigenous Herbs and Drugs, 2022)
With advances in biotechnology, genomics, and combinatorial chemistry, a wide variety of new, more potent and specific therapeutics are being created. Because of common problems such as low solubility, high potency, and/or poor stability of many of these new drugs, the means of drug delivery can impact efficacy and potential for commercialization as much as the nature of the drug itself. Thus, there is a corresponding need for safer and more effective methods and devices for drug delivery. Microspheres having particle size in range between 0.1-200 µm, can be delivered by several routes like oral, parentral, nasal, ophthalmic, transdermal, colonal etc.  In future by combining various new strategies, microspheres will find a central place in novel drug delivery, particularly in diseased cell sorting, genetic materials, safe, targeting and effective drug delivery.